In-situ curing composite positive pole piece as well as preparation method and application thereof
By using in-situ curing composite technology in the positive electrode sheet of lithium-ion battery, a polymer solid electrolyte formed by polymerization with oxidation resistant polymer monomers is solved, and the matching problem between the polymer electrolyte and the high voltage positive electrode is achieved, high energy density and good cycle stability are achieved.
Patent Information
- Application Number
- CN202411877021.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
In polymer-based solid-state batteries, there is a problem of electrochemical window mismatch between the polymer electrolyte and the high-voltage positive electrode and insufficient interface contact, resulting in a degradation of electrochemical performance and the inability to achieve high energy density and good cycling stability.
In-situ curing composite positive electrode sheets are used to form polymer solid electrolyte formed by polymerization of oxidation-resistant polymer monomers inside and on the pores of the positive electrode material, and sufficient contact between the positive electrode particles and the electrolyte film is achieved through the polymer solid electrolyte layer to avoid direct contact.
Good contact and high voltage stability between the polymer electrolyte and the high voltage positive electrode are achieved, the energy density and cycle stability of the battery are improved, and the stable cycle operation is enabled at high voltage.
Smart Images

Figure CN119695070A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to an in-situ cured composite positive electrode plate and a preparation method and application thereof. Background Art
[0002] As an electrochemical energy storage device, lithium-ion batteries have been widely used in consumer electronics, electric vehicles, energy storage and other fields. With the technological progress in related fields and the growing market demand, the development of lithium-ion batteries with higher energy density and better safety has become one of the main research and development directions.
[0003] Compared with traditional liquid lithium-ion batteries, solid-state lithium-ion batteries using solid electrolytes are compatible with metal lithium negative electrodes to achieve higher energy density. At the same time, the non-flammable properties of solid electrolytes themselves can also improve the safety of batteries. They are one of the important technical routes for the development of high-energy-density and high-safety lithium-ion batteries. Common solid electrolytes can be divided into oxides, sulfides, halides and polymers. Among them, polymer electrolytes have the characteristics of easy large-scale preparation and processing, compatibility with existing battery production processes, low cost and better interface contact compared with other types of solid electrolytes, and have been widely studied. In 2011, polyethylene oxide (PEO) electrolytes have been successfully commercialized and applied in electric vehicles. However, the electrochemical window of PEO-based polymer electrolytes is narrow, and they are often used in combination with lithium iron phosphate (LiFePO4) positive electrode materials with lower voltages, but cannot match lithium cobalt oxide (LiCoO2) and nickel cobalt manganese ternary (LiNi x Co y Mn 1-x-y O2) and other positive electrode materials, which makes it difficult for PEO-based polymer electrolyte solid-state batteries to achieve higher energy density. In addition, traditional polymer electrolytes are usually applied to batteries in the form of membranes, and their insufficient interface contact with porous composite positive electrodes will also affect the performance of the battery. Therefore, solving the problem of mismatch between polymer-based solid electrolyte membranes and high-voltage positive electrodes is of great significance for the development of polymer-based solid-state batteries with practical value.
[0004] In order to solve the problem of mismatch between polymer-based solid electrolyte and high-voltage positive electrode, two methods are mainly used in the prior art: the first is to coat the surface of the positive electrode material with oxide solid electrolyte materials, etc.; the second is to prepare a multilayer polymer electrolyte membrane, and obtain a multilayer electrolyte that is stable to high voltage and metallic lithium by layered preparation. In order to solve the problem of insufficient contact between the polymer-based solid electrolyte and the inside of the positive electrode plate, common methods include: the first is to mix the polymer electrolyte into the slurry during the preparation of the positive electrode plate, and obtain a positive electrode plate mixed with the polymer electrolyte after drying; the second is to directly apply a layer of polymer electrolyte slurry on the positive electrode plate, and obtain a positive electrode plate mixed with the polymer electrolyte after drying.
[0005] Although the method of coating the positive electrode material with a solid electrolyte can alleviate the problem of high-voltage oxidation decomposition when matching with a polymer to a certain extent, the coating process usually cannot form a complete coverage, the degree of protection is limited, and the coating layer of the oxide solid electrolyte has poor elasticity, which is difficult to adapt to the volume change that occurs during the lithium extraction process of the positive electrode material, and there are problems of separation and shedding during the electrochemical cycle. Although the double-layer electrolyte membrane can improve the problem of high-voltage instability of the polymer, the preparation process is complicated and requires multiple castings to form a film. In addition, although the method of mixing a polymer electrolyte into the positive electrode slurry can enhance the ion conductivity inside the pole piece, due to the high amount of polymer electrolyte added, it will lead to a low proportion of active materials, affecting the overall energy density of the battery. In addition, there are many holes inside the pole piece prepared by this method, and the contact between the polymer electrolyte and the positive electrode particles inside the positive electrode piece is still insufficient. The method of directly coating the polymer electrolyte slurry on the positive electrode piece also has many holes inside the pole piece after drying, and the positive electrode particles inside the pole piece are not in sufficient contact with the polymer. Insufficient contact between the polymer electrolyte and the positive electrode particles in the pole piece will lead to a serious decline in the electrochemical performance of the battery, and it is difficult to exert the high energy density of the solid-state battery.
[0006] In summary, there are electrochemical window mismatch and poor interface contact between polymer electrolyte and high voltage positive electrode. Existing solutions are difficult to effectively solve the above problems, and inevitably lead to poor electrochemical performance of solid-state batteries, inability to exert high energy density, and cumbersome preparation process. Therefore, it is urgent to improve the high voltage positive electrode plate and its preparation process so that it can be used with polymer electrolyte. Summary of the invention
[0007] The purpose of the present invention is to provide an in-situ cured composite positive electrode plate and its preparation method and application in view of the defects in the prior art. The in-situ cured composite positive electrode plate has a polymer solid electrolyte formed by in-situ initiated polymerization of oxidation-resistant polymer monomers inside and on the surface of the plate, which can not only achieve good contact between the positive electrode particles and the polymer solid electrolyte, but also the oxidation-resistant in-situ cured system polymer layer on the surface of the high-voltage positive electrode material can effectively prevent the direct contact between the polymer electrolyte membrane and the positive electrode material, thereby ensuring that the polymer solid-state battery can be stably cycled at high voltage.
[0008] To achieve the above-mentioned object, in a first aspect, the present invention provides an in-situ cured composite positive electrode sheet, comprising: a positive electrode sheet comprising a positive electrode material, a polymer solid electrolyte forming a mesh-like through-channel inside the pores of the positive electrode material, and a polymer solid electrolyte forming a polymer solid electrolyte layer on the surface of the positive electrode material;
[0009] The polymer solid electrolyte is obtained by in-situ polymerization of oxidation-resistant polymer monomers; the polymer solid electrolyte fills more than 70% of the pores inside the positive electrode material and evenly covers 100% of the surface of the positive electrode material.
[0010] Preferably, the mass percentage of the polymer solid electrolyte in the in-situ cured composite positive electrode plate is 10%-15%;
[0011] The thickness of the polymer solid electrolyte layer is less than or equal to 1 μm.
[0012] Preferably, the oxidation-resistant polymer monomer specifically includes: a monomer having a non-ether group and containing an electron-withdrawing group;
[0013] The oxidation-resistant polymer monomers include: one or more of unsaturated ester monomers, unsaturated sulfone monomers, and multi-carbon-carbon double bond cross-linking monomers.
[0014] Further preferably, the unsaturated ester monomers include: one or more of acrylate monomers, methacrylate monomers, fluorine-substituted acrylate monomers, and carbonate monomers; specifically include: one or more of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, ethyl trifluoroacrylate, tetrafluoropropyl methacrylate, hexafluorobutyl acrylate, hexafluorobutyl methacrylate, heptyl dodecafluoroacrylate, vinylene carbonate, and vinyl ethylene carbonate;
[0015] The unsaturated sulfone monomers include: one or more of methyl vinyl sulfone and ethyl vinyl sulfone;
[0016] The multi-carbon-carbon double bond cross-linking monomers include: one or more of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, poly(ethylene glycol) diacrylate, and triallyl isocyanurate.
[0017] Further preferably, the polymer solid electrolyte further comprises: one or more of a lithium salt, an additive or an initiator;
[0018] The additives include nitriles.
[0019] Preferably, the positive electrode material includes a high voltage positive electrode material; specifically includes: lithium cobalt oxide LiCoO2, lithium-rich manganese-based positive electrode material or nickel-cobalt-manganese ternary positive electrode material LiNi x Co y Mn (1-x-y) One or more of O2; 0.33≤x≤0.96, 0.02≤y≤0.33; the positive electrode material is a layered structure material.
[0020] In a second aspect, an embodiment of the present invention provides a method for preparing the in-situ cured composite positive electrode sheet as described in the first aspect, comprising:
[0021] preparing a positive electrode sheet;
[0022] Preparing a precursor solution of an in-situ curing polymer; the precursor solution comprises an oxidation-resistant polymer monomer;
[0023] The precursor solution of the in-situ curing polymer is applied to the surface of the positive electrode plate, and after standing and soaking, polymerization is initiated to polymerize the oxidation-resistant polymer monomers in the precursor solution to form an in-situ curing polymer solid electrolyte, thereby obtaining an in-situ curing composite positive electrode plate.
[0024] Preferably, the initiation polymerization specifically includes: one or more of thermal initiation polymerization, photoinitiation polymerization, and photothermal composite initiation polymerization;
[0025] Wherein, the photothermal composite initiated polymerization includes: thermal initiation combined with ultraviolet light secondary initiated polymerization, or ultraviolet initiation combined with thermal secondary initiated polymerization.
[0026] Preferably, the precursor solution further comprises: one or more of a lithium salt, an additive and an initiator;
[0027] The mass ratio of the lithium salt to the oxidation-resistant polymer monomer is 15%-35%, the mass ratio of the additive to the oxidation-resistant polymer monomer is 75%-150%, and the mass ratio of the initiator to the oxidation-resistant polymer monomer is 0.1%-1%.
[0028] In a third aspect, an embodiment of the present invention provides a polymer battery, comprising: a polymer electrolyte membrane, a negative electrode plate, and the in-situ cured composite positive electrode plate described in the first aspect or the in-situ cured composite positive electrode plate prepared by the preparation method described in the second aspect.
[0029] The in-situ cured composite positive electrode plate provided by the embodiment of the present invention has a polymer solid electrolyte formed by in-situ initiation of oxidation-resistant polymer monomer polymerization inside and on the surface of the plate. On the one hand, the oxidation-resistant polymer monomer undergoes an in-situ polymerization reaction inside the positive electrode plate to form a polymer solid electrolyte with a mesh-like through-structure. Due to the small molecular weight of the polymer monomer, it can penetrate into the pores inside the positive electrode plate, ensuring that the final polymer solid electrolyte fills more than 70% of the pores inside the positive electrode plate, which can fully ensure good solid-solid contact between the positive electrode active material particles and the polymer electrolyte; in addition, the in-situ polymerization of the polymer monomer makes the positive electrode active material particles and the polymer electrolyte adhere together to form a molecular-level contact, and there is almost no gap between the two, thereby achieving full contact between the positive electrode active material and the solid electrolyte inside the positive electrode plate, effectively constructing a continuous ion transmission path in the positive electrode plate, thereby greatly improving the ion conductivity. On the other hand, the in-situ polymerization reaction of the oxidation-resistant polymer monomers on the surface of the positive electrode piece to form a polymer solid electrolyte layer can effectively isolate the positive electrode material from the polymer electrolyte membrane, ensuring that there is no direct contact between the high-voltage positive electrode material and the polymer electrolyte membrane, thereby enabling the battery to operate normally at high voltages, such as above 4.2V, greatly improving the battery's energy density and cycle stability under high voltage; the polymer electrolyte layer on the surface of the positive electrode piece and the polymer electrolyte membrane of the solid-state battery are both polymers, so they can be directly matched with traditional solid polymer electrolyte membranes, and there is no mechanical stress between the two. Through direct bonding, hot pressing and other processes, good solid-solid contact can be ensured between the positive electrode piece and the polymer solid electrolyte membrane, ensuring the smooth transmission of lithium ions, allowing the polymer battery to stably cycle at a high cut-off charging voltage, and improving the overall energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The scanning electron microscope (SEM) images of the surface of the positive electrode sheet of Example 1 of the present invention and Comparative Example 1;
[0031] Figure 2 X-ray photoelectron spectroscopy (XPS) diagrams of the surfaces of the positive electrode sheets of Example 1 and Comparative Example 1 of the present invention;
[0032] Figure 3 is a Fourier transform infrared spectrum (FT-IR) diagram of the in-situ curing system in Example 1 of the present invention;
[0033] Figure 4The ionic conductivity data comparison is for the process of optimizing the amount of succinonitrile added in the in-situ curing system in Example 1 of the present invention;
[0034] Figure 5 The test result curve of the glass transition temperature of the in-situ curing polymerization system of the methyl methacrylate polymer with or without succinonitrile added in Example 1 of the present invention;
[0035] Figure 6 The temperature-dependent ionic conductivity test results and Arrenius fitting result curves of the optimized in-situ curing system and PEO system in Example 1 of the present invention are shown;
[0036] Figure 7 ion migration number test result curve of the optimized in-situ curing system and PEO system in Example 1 of the present invention;
[0037] Figure 8 This is a comparison diagram of density functional theory (DFT) calculation results of the HOMO energy levels of the main components of the in-situ curing system and PEO in Example 1 of the present invention;
[0038] Fig. 9 The test result curves of linear sweep voltammetry (LSV) combined with in-situ differential electrochemical mass spectrometry (DEMS) of Example 1 of the present invention and Comparative Example 1 are shown;
[0039] Fig.10 The electrochemical cycle test curves of Example 1 and Comparative Example 1 of the present invention;
[0040] Fig.11 This is the electrochemical cycle test curve of Example 2 of the present invention;
[0041] Fig.12 This is a schematic diagram of the battery structure of Example 5 of the present invention;
[0042] Fig.13 This is the electrochemical cycle test curve of Example 5 of the present invention. DETAILED DESCRIPTION
[0043] In order to facilitate a better understanding of the present invention, some technical terms are first explained below.
[0044] The technical term "in-situ curing" refers to the technology of achieving in-situ transformation from liquid phase to solid phase in the various components of the battery (positive electrode, negative electrode, separator, etc.) or the entire battery through physical (heat, light, electron beam, etc.) and chemical (electrochemical reaction, chemical reaction, etc.) means to achieve good solid-solid interface contact.
[0045] The technical term "in situ polymerization" refers to the technology of achieving in situ transformation from liquid phase to solid phase in the various components of the battery (positive electrode, negative electrode, separator, etc.) or the entire battery through chemical polymerization reactions (free radical polymerization, ionic polymerization, etc.) to achieve good solid-solid interface contact.
[0046] The technical term "high voltage positive electrode material" refers to a positive electrode material with a charge cut-off voltage above 4.2V (relative to metallic lithium).
[0047] The technical term "oxidation-resistant polymer monomer" refers to a polymerizable monomer that can stably match and work with a high-voltage positive electrode material at a high charge cut-off voltage after polymerization.
[0048] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0049] An embodiment of the present invention provides an in-situ cured composite positive electrode plate, which includes: a positive electrode plate containing a positive electrode material, a polymer solid electrolyte forming a network of through channels inside the pores of the positive electrode material, and a polymer solid electrolyte forming a polymer solid electrolyte layer on the surface of the positive electrode material; the polymer solid electrolyte is obtained by an in-situ polymerization reaction of an oxidation-resistant polymer monomer; the polymer solid electrolyte fills more than 70% of the pores inside the positive electrode material, and uniformly covers 100% of the surface of the positive electrode material.
[0050] In the above-mentioned in-situ cured composite positive electrode sheet, the polymer solid electrolyte accounts for 10%-15% of the mass percentage of the in-situ cured composite positive electrode sheet. In order to avoid increasing polarization and negatively affecting the battery capacity, the thickness of the polymer solid electrolyte layer is preferably less than or equal to 1 μm.
[0051] The above oxidation-resistant polymer monomers specifically include: monomers having non-ether groups and containing electron-withdrawing groups.
[0052] The above-mentioned oxidation-resistant polymer monomers include: one or more of unsaturated ester monomers, unsaturated sulfone monomers, and multi-carbon-carbon double bond cross-linking monomers.
[0053] The unsaturated ester monomers include: one or more of acrylate monomers, methacrylate monomers, fluorine-substituted acrylate monomers, and carbonate monomers; specifically include: one or more of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, ethyl trifluoroacrylate, tetrafluoropropyl methacrylate, hexafluorobutyl acrylate, hexafluorobutyl methacrylate, heptyl dodecafluoroacrylate, vinylene carbonate, and vinyl ethylene carbonate;
[0054] The unsaturated sulfone monomers include: one or more of methyl vinyl sulfone and ethyl vinyl sulfone;
[0055] The multi-carbon-carbon double bond cross-linking monomers include: one or more of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, poly(ethylene glycol) diacrylate, and triallyl isocyanurate.
[0056] The polymer solid electrolyte further comprises: one or more of lithium salt, additive or initiator; wherein the additive comprises nitriles.
[0057] The positive electrode material is a layered structure material, and preferably may include a high voltage positive electrode material; for example, specifically including: lithium cobalt oxide LiCoO2, lithium-rich manganese-based positive electrode material or nickel-cobalt-manganese ternary positive electrode material LiNi x Co y Mn (1-x-y) One or more of O2; 0.33≤x≤0.96, 0.02≤y≤0.33. However, the positive electrode material that can realize the technical solution of the present invention is not limited thereto, and the high voltage positive electrode material has a high energy density solid-state battery with use value.
[0058] The positive electrode sheet of the present invention can be obtained by conventional preparation processes, for example, the positive electrode active material (such as the above-mentioned high voltage positive electrode material), the binder and the conductive agent are dispersed in an organic solvent at a certain mass ratio to obtain a positive electrode slurry, which is then coated on a current collector and dried. During the process of solvent volatilization and drying, certain pores are formed inside the positive electrode sheet, and the porosity is about 15%-20%.
[0059] In the present invention, the polymer solid electrolyte of the present invention is distributed in the pores and outer surface of the positive electrode material at the same time. Among them, the polymer solid electrolyte fills more than 70% of the pores of the positive electrode material, which can be any value within the above range, such as 70%, 75%, 80%, 85%, 90%, 95%, 98%, but not limited to this. The polymer solid electrolyte is filled in the pores of the positive electrode material, and a mesh-like through-channel can be formed inside the positive electrode material, thereby effectively carrying out ion transmission and diffusion and improving ion conductivity. The porosity of the positive electrode material itself is about 15-20%. When more than 70% of it is filled with the polymer electrolyte after the polymer monomer is in-situ solidified, the polymer electrolyte is guaranteed to contact the positive electrode particles, and an effective lithium ion transmission channel can be constructed. The polymer solid electrolyte also forms a polymer solid electrolyte layer on the surface of the positive electrode material, and the preferred thickness is less than or equal to 1μm, which can be any value within the above range, such as 1μm, 0.8μm, 0.6μm, 0.5μm, 0.3μm, 0.2μm, etc. By constructing a polymer solid electrolyte layer on the surface of the positive electrode material, the high voltage positive electrode material can be isolated from the polymer electrolyte membrane of the solid-state battery. When the solid-state battery is charged to a high voltage such as 4.2V, the destruction of the polymer electrolyte membrane layer caused by the oxidation reaction of the positive electrode material can be prevented, that is, the catalytic oxidation on the surface of the positive electrode material leads to the oxidation and decomposition of the polymer chain end, resulting in gas production, interface deterioration and other problems. That is, by constructing a polymer solid electrolyte layer on the surface of the positive electrode material, the electrolyte of the solid-state battery system can be effectively protected to prevent damage to the solid battery components. At the same time, since the polymer solid electrolyte layer constructed on the surface of the positive electrode material and the electrolyte membrane of the solid-state battery are both high molecular polymers, the contact surface between the two will not generate mechanical stress between inorganic and organic, that is, no mechanical damage and destruction will occur, so that a good solid-solid contact is formed between the in-situ cured composite positive electrode plate and the electrolyte membrane, and finally the lithium ions are smoothly transmitted and diffused.
[0060] Therefore, the in-situ cured composite positive electrode plate of the present invention can not only achieve good contact between the polymer electrolyte and the high-voltage positive electrode, but also has good high-voltage stability, can be used in polymer batteries, has high energy density, good structural stability and excellent cycle performance, can be applied to lithium batteries, lithium battery packs or lithium battery modules, and is widely used in consumer electronics, electric vehicles, large-scale energy storage and other fields, and also has good application prospects in large-scale energy storage systems.
[0061] The in-situ cured composite positive electrode sheet proposed in the present invention can be prepared by the following preparation method. The main preparation steps include:
[0062] Step 1, preparing a positive electrode sheet;
[0063] The preparation method of the positive electrode sheet can be realized according to the conventional preparation process in the art.
[0064] The positive electrode material of the positive electrode sheet includes the above-mentioned high voltage positive electrode material, which will not be described in detail.
[0065] Step 2, preparing a precursor solution of an in-situ curing polymer;
[0066] The precursor solution includes an oxidation-resistant polymer monomer, which is described above and will not be described in detail. In addition, the precursor solution may also include: one or more of a lithium salt, an additive, and an initiator. The mass ratio of the lithium salt to the oxidation-resistant polymer monomer is 15%-35%, the mass ratio of the additive to the oxidation-resistant polymer monomer is 75%-150%, and the mass ratio of the initiator to the oxidation-resistant polymer monomer is 0.1%-1%.
[0067] The lithium salt includes one or more of inorganic lithium salts and organic lithium salts, specifically including one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiBOB, LiTFSI, LiDFOB, LiFSI
[0068] The additive includes nitriles, and the nitriles and oxidation-resistant polymer monomers are mixed in proportion in the precursor solution. Nitriles and oxidation-resistant polymer monomers are within the above-mentioned ratio range, which can effectively improve the ionic conductivity of the in-situ cured polymer system, reduce the glass transition temperature of the polymer system, and thus facilitate the transmission and diffusion of lithium ions. In addition, the oxidation-resistant polymer system added with the additive has a lower lithium ion migration barrier and a higher ion migration number relative to the existing polyethylene oxide (PEO) system, and is therefore more conducive to the transmission and diffusion of lithium ions. The polymer system cured in situ of the present invention is more difficult to lose electrons, thereby showing a strong oxidation ability. And unlike the PEO system, which has obvious gas production behavior, the polymer system cured in situ of the present invention has no gas production behavior before 4.2V.
[0069] Step 3, applying the precursor solution of the in-situ curing polymer to the surface of the positive electrode sheet, allowing it to stand and soak, and initiating polymerization, so that the oxidation-resistant polymer monomers in the precursor solution are polymerized to form an in-situ curing polymer solid electrolyte, thereby obtaining an in-situ curing composite positive electrode sheet.
[0070] Specifically, a precursor solution of the in-situ curing polymer is applied to the surface of the positive electrode plate and soaks the entire surface, and then allowed to stand. The monomers in the precursor solution are polymerized by light and / or heat to form an in-situ curing polymer solid electrolyte.
[0071] The initiation of polymerization specifically includes: one or more of thermal initiation polymerization, photoinitiation polymerization, and photothermal composite initiation polymerization;
[0072] The photothermal composite initiated polymerization includes: thermal initiation combined with ultraviolet light secondary initiated polymerization, or ultraviolet initiation combined with thermal secondary initiated polymerization.
[0073] The preparation method of the present invention is to apply a precursor solution containing an oxidation-resistant polymer monomer to the surface of the positive electrode plate and fully infiltrate it, and then prepare an in-situ cured composite positive electrode plate by heat and / or light-induced in-situ polymerization. The preparation method is simple, low-cost, and compatible with the existing liquid battery system manufacturing process. Through the in-situ curing technology, not only can sufficient solid-solid contact between the polymer solid electrolyte and the positive electrode active particles be achieved in the positive electrode plate, but also a continuous ion transmission path can be constructed in the plate. In addition, the composite solid-state positive electrode plate constructed by in-situ curing can make the high-voltage positive electrode material compatible with the high-voltage unstable polymer electrolyte membrane, and stable circulation can be achieved by direct bonding, which greatly increases the overall energy density of the battery.
[0074] The oxidation-resistant polymer monomer used in the preparation of the present invention is a monomer having a non-ether group and an electron-withdrawing group, including one or more of unsaturated esters, unsaturated sulfones, and multi-carbon-carbon double bond crosslinking. The use of the above-mentioned type of oxidation-resistant polymer monomer can have the advantages of a wider electrochemical window, low viscosity, good wettability, etc. The present invention uses a polymer monomer that does not contain an ether group, which can avoid severe oxidation reactions and severe side reactions when matching a high-voltage positive electrode.
[0075] The polymer solid electrolyte accounts for 10%-15% of the mass percentage of the in-situ cured composite positive electrode plate. The above mass percentage range can effectively fill more than 70% of the internal pores of the positive electrode material, and can ensure that an effective polymer solid electrolyte protective layer is formed on the positive electrode plate, thereby ensuring ion transmission performance, preventing the polymer electrolyte membrane from being oxidized under high voltage, and ensuring that the positive electrode active material has a sufficient proportion, thereby obtaining a battery with high energy density.
[0076] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0077] The reagent materials used in the following examples and comparative examples include polymer monomers, lithium salts, additives, initiators, solvents and other reagents, positive electrode active materials, negative electrode metal lithium, etc., which are all conventional reagent products obtained from the market. If no specific experimental steps or conditions are specified in the examples, the operations or conditions of conventional experimental steps in the art are followed.
[0078] Example 1
[0079] The active material of the in-situ cured composite positive electrode is LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), polymer solid electrolyte is obtained by in-situ polymerization of methyl methacrylate.
[0080] (I) Preparation of positive electrode sheet:
[0081] NCM811 material, polyvinylidene fluoride (PVDF) and conductive carbon (Super P) were dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, mixed evenly to obtain positive electrode slurry, and then applied on the carbon-coated aluminum foil with a scraper. The above aluminum foil was placed in an oven and dried at 60°C for 12 hours to remove NMP to obtain the original positive electrode sheet, which was cut into discs with a diameter of 10 mm. The active material loading of the positive electrode sheet was about 1 mg / cm 2 .
[0082] (ii) Preparing a precursor solution for in-situ curing polymer:
[0083] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium difluorooxalatoborate (LiDFOB) were dissolved in 5 ml of methyl methacrylate (MMA), wherein the concentrations of LiTFSI and LiDFOB were 0.8 M and 0.2 M, respectively. 1 g / mL of succinonitrile (SN) was added as a plasticizer, and 0.01 g / mL of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added as a photoinitiator. The mixture was stirred for 1 hour to obtain a uniform and clear precursor solution.
[0084] (III) Preparation of in-situ cured composite positive electrode sheet:
[0085] The precursor solution of the in-situ curing polymer was stirred at 5 μl / cm 2 The precursor solution was dispersed on the surface of the positive electrode plate, and after standing for 10 minutes, the plate was fully infiltrated by the precursor solution, and then cured by ultraviolet light with a wavelength of 365nm for 30 minutes to prepare an in-situ cured composite positive electrode plate.
[0086] The thickness of the polymer solid electrolyte layer of the in-situ cured composite positive electrode plate is 0.8 μm.
[0087] The electrode was scanned at -92 to 92° with a resolution of 0.6 μm voxel by micron X-ray computed tomography (CT, Zeiss Versa 515), and 1701 projection images were collected and then three-dimensional tomographic reconstruction was performed. The results showed that the porosity of the positive electrode prepared in step (i) was 15.3%, and the porosity of the in-situ cured composite positive electrode prepared in step (iii) was 3.7%. After calculation, the filling rate of the pores in the positive electrode was 75.8%.
[0088] It can be seen from the difference in mass between the positive electrode sheets in step (1) and step (3) that the mass percentage of the polymer solid electrolyte in the in-situ cured composite positive electrode sheet is about 10%.
[0089] Example 2
[0090] (I) Preparation of positive electrode sheet: same as in Example 1.
[0091] (ii) Preparing a precursor solution for in-situ curing polymer:
[0092] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium difluorooxalatoborate (LiDFOB) were dissolved in 5 ml of vinyl ethylene carbonate (VEC), wherein the concentrations of LiTFSI and LiDFOB were 0.8 M and 0.2 M, respectively. 1 g / mL of succinonitrile (SN) was added as a plasticizer, and 0.01 g / mL of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added as a photoinitiator. The mixture was stirred for 1 hour to obtain a uniform and clear precursor solution.
[0093] (III) Preparation of in-situ cured composite positive electrode sheet: Same as Example 1.
[0094] The thickness of the polymer solid electrolyte layer of the in-situ cured composite positive electrode plate is 0.9 μm.
[0095] The test was the same as in Example 1. The porosity of the positive electrode sheet prepared in step (i) was 15.3%, and the porosity of the in-situ cured composite positive electrode sheet in step (iii) was 3.5%. After calculation, the filling rate of the pores in the positive electrode sheet was 77.1%. The mass percentage of the polymer solid electrolyte in the in-situ cured composite positive electrode sheet was about 12%.
[0096] Example 3
[0097] (I) Preparation of positive electrode sheet: same as in Example 1.
[0098] (ii) Preparing a precursor solution for in-situ curing polymer:
[0099] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium difluorooxalatoborate (LiDFOB) were dissolved in 5 ml of methyl vinyl sulfone (MVS), wherein the concentrations of LiTFSI and LiDFOB were 0.8 M and 0.2 M, respectively. 1 g / mL of succinonitrile (SN) was added as a plasticizer, and 0.01 g / mL of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added as a photoinitiator. The mixture was stirred for 1 hour to obtain a uniform and clear precursor solution.
[0100] (III) Preparation of in-situ cured composite positive electrode sheet: Same as Example 1.
[0101] The thickness of the polymer solid electrolyte layer of the in-situ cured composite positive electrode plate is 1 μm.
[0102] The test was the same as in Example 1. The porosity of the positive electrode sheet prepared in step (i) was 15.3%, and the porosity of the in-situ cured composite positive electrode sheet in step (iii) was 4.3%. After calculation, the filling rate of the pores in the positive electrode sheet was 71.9%. The mass percentage of the polymer solid electrolyte in the in-situ cured composite positive electrode sheet was 11%.
[0103] Example 4
[0104] (I) Preparation of positive electrode sheet: same as in Example 1.
[0105] (ii) Preparing a precursor solution for in-situ curing polymer:
[0106] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium difluorooxalatoborate (LiDFOB) were dissolved in 5 ml of butyl acrylate (BA), wherein the concentrations of LiTFSI and LiDFOB were 0.8 M and 0.2 M, respectively. 1 g / mL of succinonitrile (SN) was added as a plasticizer, and 0.01 g / mL of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added as a photoinitiator. The mixture was stirred for 1 hour to obtain a uniform and clear precursor solution.
[0107] (III) Preparation of in-situ cured composite positive electrode sheet: Same as Example 1.
[0108] The thickness of the polymer solid electrolyte layer of the in-situ cured composite positive electrode plate is 1 μm.
[0109] The test was the same as in Example 1. The porosity of the positive electrode sheet prepared in step (i) was 15.3%, and the porosity of the in-situ cured composite positive electrode sheet in step (iii) was 3.9%. After calculation, the filling rate of the pores in the positive electrode sheet was 74.8%. The mass percentage of the polymer solid electrolyte in the in-situ cured composite positive electrode sheet was 11%.
[0110] Example 5
[0111] (I) Preparation of positive electrode sheet:
[0112] NCM811 material, polyvinylidene fluoride (PVDF) and conductive carbon (Super P) were dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, mixed evenly to obtain positive electrode slurry, and then applied on the carbon-coated aluminum foil with a scraper. The above aluminum foil was placed in an oven and dried at 60°C for 12 hours to remove NMP to obtain the original positive electrode sheet, which was cut into 73mm×60mm sheets. The active material loading of the positive electrode sheet was about 1mg / cm 2 .
[0113] (ii) Preparing a precursor solution for in-situ curing polymer: Same as Example 1.
[0114] (III) Preparation of in-situ cured composite positive electrode sheet: Same as Example 1.
[0115] The thickness of the polymer solid electrolyte layer of the in-situ cured composite positive electrode plate is 0.8 μm.
[0116] The test was the same as in Example 1. The porosity of the positive electrode sheet prepared in step (i) was 15.3%, and the porosity of the in-situ cured composite positive electrode sheet in step (iii) was 3.6%. After calculation, the filling rate of the pores in the positive electrode sheet was 76.5%. The mass percentage of the polymer solid electrolyte in the in-situ cured composite positive electrode sheet was 10%.
[0117] Example 6
[0118] (I) Preparation of positive electrode sheet:
[0119] NCM811 material, polyvinylidene fluoride (PVDF) and conductive carbon (Super P) were dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, mixed evenly to obtain positive electrode slurry, and then applied on the carbon-coated aluminum foil with a scraper. The above aluminum foil was placed in an oven and dried at 60°C for 12 hours to remove NMP to obtain the original positive electrode sheet, which was cut into 73mm×60mm sheets. The active material loading of the positive electrode sheet was about 1mg / cm 2 .
[0120] (ii) Preparing a precursor solution for in-situ curing polymer: Same as Example 2.
[0121] (III) Preparation of in-situ cured composite positive electrode sheet: same as in Example 2.
[0122] The thickness of the polymer solid electrolyte layer of the in-situ cured composite positive electrode plate is 0.9 μm.
[0123] The test was the same as in Example 1. The porosity of the positive electrode sheet prepared in step (i) was 15.3%, and the porosity of the in-situ cured composite positive electrode sheet in step (iii) was 3.5%. After calculation, the filling rate of the pores in the positive electrode sheet was 77.1%. The mass percentage of the polymer solid electrolyte in the in-situ cured composite positive electrode sheet was 12%.
[0124] Comparative Example 1
[0125] The positive electrode sheet was prepared by adopting step (1) of Example 1.
[0126] Comparative Example 2
[0127] NCM811 material, polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and conductive carbon (Super P) were dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 8:0.73:0.27:1, mixed evenly to obtain a positive electrode slurry, and then applied on a carbon-coated aluminum foil with a scraper. The above aluminum foil was placed in an oven and dried at 60°C for 12 hours to remove NMP, and a positive electrode sheet of a blended polymer solid electrolyte was obtained, which was cut into a disc with a diameter of 10 mm. The active material loading of the positive electrode sheet was about 1 mg / cm 2 .
[0128] Comparative Example 3
[0129] NCM811 material, polyvinylidene fluoride (PVDF) and conductive carbon (Super P) are dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, mixed evenly to obtain a positive electrode slurry, and applied to the carbon-coated aluminum foil with a scraper. The above aluminum foil is placed in an oven and dried at 60°C for 12 hours to remove NMP to obtain the original positive electrode plate, and then PEO and LiTFSI are dissolved in it at mass fractions of 275 mg / ml and 100 mg / ml respectively to prepare a polymer electrolyte slurry, and the slurry is evenly applied to the original positive electrode plate by a scraper, and then placed in an oven at 60°C for 12 hours to remove acetonitrile to obtain a positive electrode plate filled with a solid electrolyte, which is cut into a disc with a diameter of 10 mm. The active material loading of the positive electrode plate is about 1 mg / cm 2 .
[0130] Comparative Example 4
[0131] NCM811 material, polymethyl methacrylate (PMMA), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), succinonitrile (SN) and conductive carbon (Super P) were dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 8:0.43:0.14:0.43·:1, mixed evenly to obtain a positive electrode slurry, and applied on a carbon-coated aluminum foil with a scraper. The above aluminum foil was placed in an oven and dried at 60°C for 12 hours to remove NMP, and a positive electrode sheet of a blended polymer solid electrolyte in the positive electrode was obtained, which was cut into a disc with a diameter of 10 mm. The active material loading of the positive electrode sheet was about 1 mg / cm 2 .
[0132] Comparative Example 5
[0133] The positive electrode plate was prepared by adopting step (a) of Example 5.
[0134] Hereinafter, the performance of the positive electrode sheets obtained in each embodiment and comparative example is characterized, and batteries are assembled and tested.
[0135] Performance parameter characterization:
[0136] 1. Morphology characterization:
[0137] The original positive electrode sheet of step (i) of Example 1 and the composite positive electrode sheet after in-situ curing in step (iii) were morphologically characterized.
[0138] Figure 1 is a scanning electron microscopy (SEM) image, where Figure 1 (a) is the SEM image of the original positive electrode sheet. Figure 1 (b) is the SEM image of the composite positive electrode sheet after in-situ curing. Figure 1 It can be seen that Figure 1 The original positive electrode sheet (a) has positive electrode particles distributed on the surface, and the composite positive electrode sheet after applying the precursor solution of the in-situ curing polymer to the surface of the positive electrode sheet and initiating in-situ polymerization to form a uniform polymer solid electrolyte layer on the surface of the positive electrode sheet in step (ii) and step (iii) of Example 1 is as follows: Figure 1 As shown in (b), there is no granular material on the surface of the electrode, which indicates that the surface of the positive electrode is completely covered by a uniform polymer solid electrolyte layer.
[0139] Figure 2 This is the surface X-ray photoelectron spectroscopy (XPS) analysis diagram. Figure 2 XPS analysis was performed on the original positive electrode sheet of Example 1 and the composite positive electrode sheet after in-situ curing. Figure 2As shown in (c), it can be observed from the XPS O1s spectrum that the original positive electrode sheet obtained in step (i) of Example 1 has a signal of lattice oxygen of the positive electrode material at the position of 529 eV, but the surface of the in-situ cured composite electrode sheet obtained after steps (ii) and (iii) cannot detect the signal of lattice oxygen from the positive electrode material, which indicates that the surface of the positive electrode material is completely covered by the polymer electrolyte. In addition, Figure 2 (d) As shown in the Ni 2p spectrum, it can be seen that the original positive electrode obtained in step (i) of Example 1 has Ni2P at 854eV and 871eV. 3 / 2 and Ni2P 1 / 2 The peak position signal from NCM811 and its satellite peak signals are detected on the surface of the in-situ cured composite positive electrode sheet obtained after step (ii) and step (iii), but the Ni signal from the positive electrode material cannot be detected on the surface of the in-situ cured composite positive electrode sheet obtained after step (ii) and step (iii), which further indicates that the surface of the positive electrode sheet prepared by the in-situ curing method is uniformly coated with the polymer solid electrolyte. Therefore, the peak position signal from NCM811 is completely undetectable on the surface of the in-situ cured composite electrode sheet obtained after step (ii) and step (iii) of Example 1, indicating that the surface of the positive electrode material is completely and uniformly coated with the polymer solid electrolyte layer.
[0140] 2. Component characterization:
[0141] Figure 3 It is a Fourier transform infrared spectroscopy (FTIR) analysis diagram of the monomers methyl methacrylate (MMA), succinonitrile (SN) and precursor solution before and after polymerization in Example 1.
[0142] like Figure 3 As shown in the figure, it can be seen that the precursor solution and the monomer methyl methacrylate (MMA) before polymerization are both at 1650 cm -1 There is a C=C signal peak at 1650cm -1 The C=C signal at 2250cm -1 The characteristic peak at corresponds to the C≡N vibration peak of the succinonitrile component, and the peak position has not shifted, indicating that succinonitrile does not react with other components in the precursor solution and can stably exist in the precursor solution. Example 1 The polymerization reaction is carried out by ultraviolet light curing, and its curing mechanism is a free radical polymerization reaction initiated by ultraviolet light.
[0143] 3. Characterization of physical and chemical properties:
[0144] The lithium ion transport characteristics of the in-situ solidified components and the test results on the positive electrode stability are as follows Figure 4-9 shown. Figure 4 is the ionic conductivity of the in-situ curing components with different succinonitrile contents; Figure 5The test results of glass transition temperature of the polymer system containing 1g / ml succinonitrile in-situ curing component and no succinonitrile component; Figure 6 The ionic conductivity comparison and Arrenius fitting results of the in-situ curing component containing 1g / ml succinonitrile and PEO; Figure 7 The ion migration number test results of PEO and the in-situ curing component containing 1g / ml succinonitrile; Figure 8 HOMO and LUMO calculation results of the main components and PEO in the in-situ curing system; Fig. 9 DEMS test results of matching PEO electrolyte with original positive electrode sheet (9a) and in-situ cured positive electrode sheet (9b) respectively.
[0145] Figure 4 The ionic conductivity of the in-situ cured component system when different succinonitrile contents were added to the precursor solution is shown in the figure. The resistance value was obtained by assembling a stainless steel-to-stainless steel symmetrical cell and performing an electrochemical impedance spectroscopy (EIS) test on a ZAHNER IM6 electrochemical workstation. The test frequency range was 10 6 -1Hz, applied bias voltage is 5mV, and ionic conductivity is calculated by the following formula:
[0146] Where d is the electrolyte thickness, S is the electrolyte contact area, and R is the resistance value measured by EIS.
[0147] Figure 4 MS0.4 means that the amount of succinonitrile added to methyl methacrylate is 0.4 g / ml (i.e., the amount of succinonitrile added to each ml of methyl methacrylate is 0.4 g), and its ionic conductivity at 60°C is 2.2×10 -7 S / cm; MS0.6 means that the amount of succinonitrile added to methyl methacrylate is 0.6 g / ml, and its ionic conductivity at 30°C and 60°C is 6.7×10 -8 S / cm and 1.1×10 -7 S / cm; MS0.8 means that the amount of succinonitrile added to methyl methacrylate is 0.8 g / ml, and its ionic conductivity at 30°C and 60°C is 2.6×10 -6 S / cm and 1.6×10 -5 S / cm; MS1.0 means that the amount of succinonitrile added to methyl methacrylate is 1 g / ml, and its ionic conductivity at 30°C and 60°C is 1.3×10 -4 S / cm and 1.1×10 -3 S / cm. The ionic conductivity of methyl methacrylate monomer itself is low when in-situ curing occurs. Therefore, when methyl methacrylate is used as a polymerization monomer to construct an in-situ curing system, succinonitrile is added as a plasticizer to improve its ionic conductivity.
[0148] When the addition amount of succinonitrile is lower than the ratio of 0.4g:1ml, the effective ionic conductivity data cannot be obtained due to the poor contact between the system itself and the stainless steel test electrode; as the addition amount of succinonitrile increases, the ionic conductivity of the precursor system also increases. When the addition amount reaches a mass fraction of 1g:1ml, the ionic conductivity of the system at 30°C can reach 0.133mScm -1 , can reach 1.1mScm at 60℃ -1 , fully meeting the requirements for ionic conductivity when the battery is running at room temperature and 60°C. Through the above optimization process, we believe that when the mass percentage of the additive relative to the polymer monomer is in the range of 75%-150%, better ionic conductivity can be obtained. Therefore, in the embodiment of the present invention, the system of 1g / ml of succinonitrile added to methyl methacrylate (i.e., 1g of succinonitrile added per ml of methyl methacrylate, i.e., 100% by mass) is selected as the analysis system for DSC test, variable temperature ionic conductivity test, Arrenius fitting results, ion migration number, density functional theory calculation, linear sweep voltammetry (LSV) and in-situ differential electrochemical mass spectrometry (DEMS).
[0149] like Figure 5 As shown, Figure 5 In the figure, PMMA represents a polymer of methyl methacrylate, and PMS represents a polymer of methyl methacrylate to which 1 g / ml of succinonitrile is added. By testing with a scanning rate of 5 K / min from -15°C to 95°C by DSC (Netzsch DSC 214 Polyma), it can be seen that the glass transition temperature of methyl methacrylate after polymerization is about 64°C, but the glass transition temperature of the polymer obtained by adding succinonitrile according to the mass ratio of succinonitrile:methyl methacrylate is 1 g / ml is about 50°C. It can be seen that when succinonitrile is added to the polymerization precursor system, the glass transition temperature of the in-situ cured system can be effectively reduced, and the reduction in the glass transition temperature can effectively improve the mobility of the polymer chain segments, thereby improving the lithium ion transport capacity of the polymer solid electrolyte and effectively improving the ionic conductivity. Therefore, this embodiment enhances the segment motion of the in-situ cured polymerization system by adding succinonitrile to the polymer system, thereby improving its ionic conductivity.
[0150] Furthermore, the resistance values were obtained by assembling stainless steel-stainless steel symmetrical cells and performing electrochemical impedance spectroscopy (EIS) on a ZAHNER IM6 electrochemical workstation at different temperatures. The test frequency range was 10 6 -1Hz, applied bias voltage is 5mV, and ionic conductivity is calculated by the following formula:
[0151] Where d is the electrolyte thickness, S is the electrolyte contact area, and R is the resistance value measured by EIS.
[0152] The Arrenius fit is performed using the following formula:
[0153] A is the pre-factor, Ea is the Arrhenius activation energy; T is the absolute temperature; R is the molar gas constant.
[0154] like Figure 6 As shown, the temperature-variable ionic conductivity test and Arrenius fitting results of polyethylene oxide (PEO) and the polymer (PMS) of methyl methacrylate with 1g / ml succinonitrile added in the present invention show that the migration barrier of the PMS in-situ curing polymer system is 0.429eV, while the barrier of the PEO system is 0.969eV. The migration barrier of the in-situ curing polymer system PMS of the present invention is about 0.54eV lower than that of the conventional PEO system. The lithium ion migration barrier in the in-situ curing system of the present invention is lower, which is more conducive to the transport of lithium ions. This fully demonstrates that the polymer solid electrolyte system of the present invention has excellent lithium ion transport capacity.
[0155] The ion migration number was tested by assembling a lithium-lithium symmetric battery using a DC polarization method. The results are as follows Figure 7 As shown, the DC polarization bias is 10mV, and the EIS test frequency range before and after polarization is 10 6 -1Hz, applied bias voltage is 5mV, resistance value is fitted by Zview and ion migration number is calculated by the following formula:
[0156]
[0157] The test results of the ion migration number of polyethylene oxide (PEO) and the polymer of methyl methacrylate (PMS) with 1g / ml succinonitrile added in the present invention show that the ion migration number of the PMS in-situ curing system is 0.297, while the ion migration number of the PEO system is 0.156. The ion migration number of the in-situ curing polymer system PMS of the present invention is 0.141 higher than that of the PEO system, which shows that the in-situ curing system of the present invention has a high ion migration number. The higher the ion migration number, the higher the proportion of lithium ion migration. Therefore, when the in-situ solid-state curing system of the present invention is applied to the positive electrode sheet, it has a higher ion migration number than the conventional system, and the lithium ion contributes more to the overall ion transport.
[0158] Density functional theory (DFT) calculations were performed using Gaussian 09, and the molecular geometry was optimized using the B3LYP level and 6-311G (d, p) basis set, such as Figure 8As shown. According to the mass ratio of succinonitrile: methyl methacrylate 1g / ml, an in-situ curing system is obtained, wherein the HOMO energy levels of the main components methyl methacrylate and succinonitrile are -7.23eV and -9.51eV respectively, and the HOMO energy level of the minimum repeating unit of PEO is -6.99eV. Molecules with low HOMO energy levels are more difficult to lose electrons and show stronger oxidation ability. It can be seen that the energy levels of each component in the system of the present invention are significantly lower than the HOMO energy level of PEO, which shows that each component in the in-situ curing system of the present invention has better oxidation resistance.
[0159] Fig. 9 Linear sweep voltammetry (LSV) and in-situ differential electrochemical mass spectrometry (DEMS) of polyethylene oxide (PEO) and the polymer of methyl methacrylate (PMS) with 1 g / ml succinonitrile added thereto. The specific test process is: assemble the battery using a homemade electrochemical in-situ DEMS test mold, perform LSV test at 60°C at a scan rate of 0.1 mV / s while testing DEMS. Combining the LSV and DEMS tests, we can see that: Fig. 9 The left figure shows the solid-state battery obtained by matching the original positive electrode sheet and the PEO electrolyte membrane obtained in step (I) of Example 1. At 3.91V, a gas production peak with a charge-to-mass ratio of 29 appears, which is a signal of early decomposition of PEO. The gas production peak corresponds to the alkyl fragment CH3CH2 produced by the induced cracking of the terminal oxygen atom of PEO after losing electrons. + signal; Fig. 9 The middle right figure is a solid-state battery obtained by matching the in-situ cured composite positive electrode plate with the PEO electrolyte after the final step (three) of Example 1. No early PEO decomposition and gas production were observed, which indicates that the polymer electrolyte layer on the surface of the in-situ cured composite positive electrode can isolate the positive electrode material from the PEO electrolyte membrane, significantly improving the oxidation resistance of the polymer electrolyte to the high-voltage positive electrode, thereby effectively widening the electrochemical window of the polymer solid-state battery, improving the energy density of the solid-state battery, and greatly improving the cycle stability of the solid-state battery under high voltage.
[0160] 4. Electrochemical performance test:
[0161] Electrochemical tests were performed on each embodiment and comparative example:
[0162] The polyethylene oxide (PEO) polymer electrolyte membrane used in all the embodiments and comparative examples of the present invention is homemade and is specifically prepared by the following process:
[0163] PEO polymer and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were dissolved in acetonitrile solution at a mass ratio of 2.75:1 and stirred for 24 hours to obtain a uniform solution. The solution was then poured into a polytetrafluoroethylene mold, dried for 24 hours and transferred to a vacuum oven for further drying at 60°C for 24 hours. After demolding, a PEO polymer electrolyte membrane was obtained.
[0164] The positive electrode sheets of Examples 1-4 and Comparative Examples 1-4 constitute CR2023 button batteries. The specific steps for making the button batteries are as follows:
[0165] A CR2023 button cell was assembled with metallic lithium as the negative electrode, the pole pieces obtained in each embodiment and comparative example as the positive electrode, and a PEO polymer electrolyte membrane as the intermediate membrane, thus obtaining a PEO-based polymer solid button cell.
[0166] Electrochemical charge and discharge test of assembled CR2023 button cells:
[0167] 0.5C cycle performance test at 60°C: The PEO-based polymer solid button batteries assembled in Example 1, Example 2 and Comparative Example 1 were tested using a blue electric tester. The prepared button batteries were placed in a high-temperature oven at 60°C for charge and discharge tests. The voltage range was 2.8V-4.2V. First, they were activated for 3 cycles at 0.1C, and then charged and discharged at 0.5C constant current. The test results are as follows: Fig.10 , Fig.11 And as shown in Table 1.
[0168] Table 1 shows the cycle performance of button cells at 0.5C current density at 60°C.
[0169]
[0170] The polymer monomers in Examples 1-4 are methyl methacrylate (MMA), vinyl ethylene carbonate (VEC), methyl vinyl sulfone (MVS) and butyl acrylate (BA), respectively. The in-situ cured composite positive electrode plates obtained in each Example are assembled to obtain a polymer solid-state battery. The first discharge capacities at 0.1C are 188.5 mAh / g, 181 mAh / g, 177 mAh / g, and 170.4 mAh / g, respectively. The first discharge capacities at 0.5C are 169.7 mAh / g, 164.4 mAh / g, 161 mAh / g, and 15 The discharge capacities after 300 cycles at 2.5mAh / g and 0.5C are 139.7mAh / g, 128.3mAh / g, 130.3mAh / g and 135.6mAh / g, with capacity retention rates of 82.4%, 78%, 80.9% and 88.9%, respectively. The discharge capacities after 500 cycles at 0.5C are 125.8mAh / g, 114.5mAh / g, 108.7mAh / g and 118.3mAh / g, with capacity retention rates of 74.1%, 69.7%, 67.5% and 77.6%, respectively. In general, the in-situ composite positive electrode sheet obtained by the present invention has a high initial discharge specific capacity and excellent high-temperature cycle stability and capacity retention rate when assembled into a solid battery. After cycling for 300 weeks at 60°C, it has a discharge specific capacity of more than 125 mAh / g and a capacity retention rate of more than 75%; after cycling for 500 weeks, it still has a discharge specific capacity of more than 100 mAh / g and a capacity retention rate of more than 65%.
[0171] The positive electrode sheet of Comparative Example 1 is the original positive electrode sheet in step (a) of Example 1, and it is assembled to obtain a polymer solid-state battery, whose first discharge capacity at 0.1C is 176.5mAh / g, the first discharge capacity at 0.5C is 162.8mAh / g, the discharge capacity after 300 cycles at 0.5C is 45.6mAh / g, and the capacity retention rate is 28%. The assembled battery cannot be cycled to 500 weeks. Compared with Comparative Example 1, the polymer solid-state battery assembled from the composite positive electrode sheet of Example 1 has an increase of 12mAh / g in the first discharge capacity at 0.1C, an increase of 6.9mAh / g in the first discharge capacity at 0.5C, an increase of 94.1mAh / g in the discharge capacity after 300 cycles at 0.5C, and an increase of 54.4% in the capacity retention rate. The discharge capacity of the polymer solid-state battery assembled in Example 1 after 500 cycles at 0.5C is 125.8mAh / g, and the capacity retention rate is still as high as 74.1%. This fully demonstrates that the composite positive electrode plate of the present invention has excellent cycle stability under high voltage due to the in-situ solidified polymer electrolyte inside the pores and on the surface. The solid-state battery containing the composite positive electrode plate can be effectively cycled for more than 500 weeks, has good capacity retention rate, and has practical value.
[0172] In Comparative Examples 2-4, non-in-situ cured polymers were used to modify the positive electrode sheets. In Comparative Example 2, PEO and lithium salt were mixed in the preparation process of the positive electrode sheet, thereby directly obtaining a composite positive electrode sheet with a mixed polymer electrolyte. In Comparative Example 3, a mixed slurry of PEO and lithium salt was directly coated on the surface of the positive electrode sheet and dried to obtain a composite positive electrode sheet. In Comparative Example 4, poly-PMMA, lithium salt and additive SN were mixed in the preparation process of the positive electrode sheet, thereby directly obtaining a composite positive electrode sheet with a mixed polymer electrolyte. The composite positive electrode sheets of Comparative Examples 2-4 were assembled to obtain polymer solid-state batteries, wherein the polymer solid-state batteries of Comparative Examples 2-3 had initial discharge capacities of 160.2 mAh / g and 166.7 mAh / g at 0.1C, 154.6 mAh / g and 162.6 mAh / g at 0.5C, and 39.8 mAh / g and 93.5 mAh / g after 300 cycles at 0.5C, respectively. The capacity retention rates were 25.7% and 57.5%, and the assembled batteries could not be cycled for 500 cycles. The polymer solid-state battery of Comparative Example 4 was in an open circuit state and could not work normally. Compared with Comparative Examples 2 and 3, the first discharge capacity of Example 1 at 0.1C increased by 28.3mAh / g and 21.8mAh / g, respectively, and the first discharge capacity at 0.5C increased by 15.1mAh / g and 7.1mAh / g, respectively, and the discharge capacity after 300 cycles at 0.5C increased by 99.9mAh / g and 46.2mAh / g, respectively, and the capacity retention rate increased by 56.7% and 24.9%, respectively. The discharge capacity of Example 1 after 500 cycles at 0.5C was 125.8mAh / g, and the capacity retention rate was still as high as 74.1%, while the solid-state batteries assembled in Comparative Examples 2-4 could not be cycled for 500 weeks. This fully shows that the composite positive electrode plate of the present invention has significantly improved cycle stability under high voltage, longer cycle life and higher capacity retention rate compared with the non-in-situ cured positive electrode plate, that is, the positive electrode plate directly mixed or coated with a polymer electrolyte. This shows that the use of in-situ curing can obtain a solid-state battery with significantly improved electrochemical performance.
[0173] It can be seen that the in-situ cured composite positive electrode plate of the present invention has been significantly improved in terms of first discharge capacity and cycle performance. Therefore, the present invention constructs an in-situ cured composite positive electrode plate, and the internal pores and surface of the positive electrode material have a polymer solid electrolyte, and assembles it into a PEO-based all-solid-state battery. The capacity retention rate is as high as 88.9% after 300 cycles at 60°C, and the capacity retention rate after 500 cycles is also 77.6%. After long cycles, it has a high capacity retention rate, and has very good high-voltage cycle stability and long cycle life. The composite positive electrode plate of the present invention can significantly improve the high-voltage cycle performance of polymer-based solid-state lithium-ion batteries that match high-voltage positive electrode materials, thereby significantly improving the energy density and cycle life of polymer-based all-solid-state lithium-ion batteries, making the application prospects of polymer-based all-solid-state lithium-ion batteries.
[0174] The positive electrode sheets of Examples 5-6 and Comparative Example 5 are assembled into soft-pack batteries. The specific production steps are as follows:
[0175] Metal lithium is used as the negative electrode, the pole pieces obtained in Examples 5-6 and Comparative Example 5 are used as the positive electrode, and the PEO polymer electrolyte membrane is used as the intermediate membrane. The sizes of the intermediate membranes are 75mm×62mm, 73mm×60mm, and 76mm×63mm, respectively. First, the positive and negative electrodes are welded to the pole ears, and then the positive pole piece, the PEO polymer electrolyte membrane, and the negative pole piece are directly stacked together and placed in an aluminum-plastic bag. They are evacuated and heat-sealed by a vacuum heat-sealing device to assemble into a soft-pack battery. The structure is as follows: Fig.12 The PEO polymer electrolyte membrane is obtained by the above-mentioned preparation process.
[0176] Electrochemical charge and discharge tests on assembled soft pack batteries:
[0177] 0.1C cycle performance test at 60°C: The PEO-based polymer solid soft-pack batteries in Examples 5-6 and Comparative Example 5 were tested using a blue electric tester. The prepared soft-pack batteries were placed in a high-temperature oven at 60°C for charge and discharge tests, with a voltage range of 2.8V-4.2V. The electrochemical cycle performance of the battery in Example 5 is shown in Figure 2. Fig.13As shown, its first-week discharge capacity is 168.8 mAh / g, and the capacity after 30 weeks of stable circulation without additional external pressure is as high as 155.0 mAh / g. The first discharge capacity of the soft-pack battery assembled in Example 6 is 163.0 mAh / g, and the capacity after 30 weeks of stable circulation without additional external pressure is as high as 148.5 mAh / g, while the battery in Comparative Example 5 cannot be cycled under the same working conditions. It can be seen that the composite positive electrode sheet of the present invention still has a high first-week discharge capacity and excellent high-voltage cycle stability when assembled into a soft-pack battery, while the soft-pack battery assembled without the modified positive electrode sheet cannot perform effective electrochemical cycles.
[0178] It can be seen that the in-situ cured composite positive electrode electrode of the present invention has a polymer solid electrolyte formed by in-situ initiation of polymerization of oxidation-resistant polymer monomers inside and on the surface of the electrode, which can not only achieve good contact between the polymer electrolyte and the high-voltage positive electrode, but also has good high-voltage stability.
[0179] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An in-situ cured composite positive electrode sheet, characterized in that: The in-situ cured composite positive electrode sheet comprises: a positive electrode sheet containing a positive electrode material, a polymer solid electrolyte forming a mesh-like through-channel inside the pores of the positive electrode material, and a polymer solid electrolyte forming a polymer solid electrolyte layer on the surface of the positive electrode material; The polymer solid electrolyte is obtained by in-situ polymerization of oxidation-resistant polymer monomers; the polymer solid electrolyte fills more than 70% of the pores inside the positive electrode material and evenly covers 100% of the surface of the positive electrode material.
2. The in-situ cured composite positive electrode sheet according to claim 1, characterized in that: The mass percentage of the polymer solid electrolyte to the in-situ cured composite positive electrode plate is 10%-15%; The thickness of the polymer solid electrolyte layer is less than or equal to 1 μm.
3. The in-situ cured composite positive electrode sheet according to claim 1, characterized in that: The oxidation-resistant polymer monomer specifically includes: a monomer having a non-ether group and containing an electron-withdrawing group; The oxidation-resistant polymer monomers include: one or more of unsaturated ester monomers, unsaturated sulfone monomers, and multi-carbon-carbon double bond cross-linking monomers.
4. The in-situ cured composite positive electrode sheet according to claim 3, characterized in that: The unsaturated ester monomers include: one or more of acrylate monomers, methacrylate monomers, fluorine-substituted acrylate monomers, and carbonate monomers; specifically include: one or more of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, ethyl trifluoroacrylate, tetrafluoropropyl methacrylate, hexafluorobutyl acrylate, hexafluorobutyl methacrylate, dodecafluoroheptyl acrylate, vinylene carbonate, and vinyl ethylene carbonate; The unsaturated sulfone monomers include: methyl vinyl sulfone and / or ethyl vinyl sulfone; The multi-carbon-carbon double bond cross-linking monomers include: one or more of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, poly(ethylene glycol) diacrylate, and triallyl isocyanurate.
5. The in-situ cured composite positive electrode sheet according to claim 3, characterized in that: The polymer solid electrolyte further comprises: one or more of a lithium salt, an additive or an initiator; The additives include nitriles.
6. The in-situ cured composite positive electrode sheet according to claim 1, characterized in that: The positive electrode material includes a high voltage positive electrode material; specifically includes: lithium cobalt oxide LiCoO2, lithium-rich manganese-based positive electrode material or nickel-cobalt-manganese ternary positive electrode material LiNi x Co y Mn (1-x-y) One or more of O2; 0.33≤x≤0.96, 0.02≤y≤0.33; the positive electrode material is a layered structure material.
7. A method for preparing an in-situ cured composite positive electrode sheet according to any one of claims 1 to 6, characterized in that: The preparation method comprises: preparing a positive electrode sheet; Preparing a precursor solution of an in-situ curing polymer; the precursor solution comprises an oxidation-resistant polymer monomer; The precursor solution of the in-situ curing polymer is applied to the surface of the positive electrode plate, and after standing and soaking, polymerization is initiated to polymerize the oxidation-resistant polymer monomers in the precursor solution to form an in-situ curing polymer solid electrolyte, thereby obtaining an in-situ curing composite positive electrode plate.
8. The preparation method according to claim 7, characterized in that: The initiation polymerization specifically includes: one or more of thermal initiation polymerization, photoinitiation polymerization, and photothermal composite initiation polymerization; Wherein, the photothermal composite initiated polymerization includes: thermal initiation combined with ultraviolet light secondary initiated polymerization, or ultraviolet initiation combined with thermal secondary initiated polymerization.
9. The preparation method according to claim 7, characterized in that: The precursor solution further comprises: one or more of a lithium salt, an additive and an initiator; The mass ratio of the lithium salt to the oxidation-resistant polymer monomer is 15%-35%, the mass ratio of the additive to the oxidation-resistant polymer monomer is 75%-150%, and the mass ratio of the initiator to the oxidation-resistant polymer monomer is 0.1%-1%.
10. A polymer battery, characterized in that: The polymer battery comprises a polymer electrolyte membrane, a negative electrode plate, and an in-situ cured composite positive electrode plate according to any one of claims 1 to 6 or an in-situ cured composite positive electrode plate prepared by the preparation method according to any one of claims 7 to 9.
Citation Information
Patent Citations
In-situ polymerized organic-inorganic composite solid-state battery
CN111933894A
Solid-state battery based on plastic crystal modified positive electrode and preparation method of solid-state battery
CN114335536A
Novel positive electrode structure, preparation method thereof and battery
CN114464765A
Novel semi-solid battery and preparation method thereof
CN114765273A
Cathode active material composite, secondary battery cathode comprising same, and secondary battery comprising same
US20240304794A1
Cited By
Preparation method and application of artificially modified CEI material layer
CN121483985A
Preparation method of artificial modified CEI material layer and application thereof
CN121483985B
High-voltage-resistant composite positive plate for inhibiting cyclic gas production of battery and preparation method of high-voltage-resistant composite positive plate
CN122291407A